PERANCANGAN DAN IMPLEMENTASI APLIKASI PENGGAJIAN BERBASIS DEKSTOP PADA MURNI SADAR ENGLISH COURSE - Victor Marudut Mulia Siregar; Heru Sugara (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2018)
This study aims to create a Desktop Based Payroll Application for Conscious Pure English Course institutions. Payroll calculations on the company are carried out on a monthly basis, Payroll recording and reporting on the Pure Sadar English Language Course still uses the semi-computerized method of using Microsoft Excel which is considered not fulfilling in dealing with payroll problems because there are still frequent salary calculation errors. Considering that there are quite a lot of employee payroll transactions, a payroll application is designed, which is expected to be able to help companies achieve their goals effectively and efficiently.